The Implementation of Task-Based Digital Storytelling to Enhance Students’ Speaking Competency in Primary School - Ni Kadek Winda Hapsari Dewi; Ni Made Ratminingsih; Luh Gede Eka Wahyuni (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
This study aims to investigate the effect of implementing Task-Based Digital Storytelling through the Technology-Mediated Task-Based Language Teaching (TMTBLT) approach on improving primary school students’ speaking competency. This research employed a quantitative approach using a pre-experimental design with a one-group pre-test and post-test model. The participants of this study were 36 sixth-grade students at a primary school in Bali. Data were collected through speaking tests administered as pre-test and post-test and assessed using a speaking rubric covering pronunciation, grammar, vocabulary, fluency, and comprehension. The data were analyzed using descriptive statistics, normality testing, and a paired sample t-test. The findings revealed a significant improvement in students’ speaking competency after the implementation of Task-Based Digital Storytelling. The mean score increased from 59.44 in the pre-test to 75.89 in the post-test. The paired sample t-test result showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between students’ speaking performance before and after the intervention. These findings suggest that Task-Based Digital Storytelling within the TMTBLT framework is an effective instructional strategy to enhance primary school students’ speaking competency and to create a more interactive and meaningful language learning environment.